Major project in the field of education in Latin America and the Caribbean: progress, limitations, obstacles and challenges: working document (UNESCO ParisFR, 1991)
Reviews the decade 1980-1990 and stresses the fact that education systems have succeeded in maintaining their quantitative achievements at a high cost in terms of quality and equity. Identifies points where alternatives must be found in order to raise the level of efficiency. Looks at the challenge that education systems of the region will have to meet in their future development and the main stages for tackling it appropriately.
DC